Inflation, Financial Developments, and Wealth Distribution - Ho, Wai-Yip Alex (IMF Working Papers; Working Paper ;, 2016)
We find that from 1995 to 2002 in China, the dispersion of wealth decreased, the moneywealth ratio increased for all wealth levels and the aggregate money-output ratio increased. We develop a two-asset dynamic general equilibrium model in which households face a portfolio adjustment cost and a borrowing constraint. We find that financial development lowers the dispersion of wealth by reducing the precautionary motive of households. In addition, tight monetary policies increase the value of money and thus increase the moneywealth ratio for all wealth levels and the aggregate money-output ratio.